Analysis of an experience of statistics topics with hypermedia technology for teachers' training - José María CHAMOSO SÁNCHEZ; Juan Francisco GARCÍA SÁNCHEZ; M. RODRÍGUEZ SÁNCHEZ (Ediciones Universidad de Salamanca, 2009)
It is presented an experience in which is used hypermedia as a tool for education of teachers. More exactly, university students to be school teachers, with university computer science students, design and implement statistics topics with medium hypermedia with the aim that the future teachers must organize their teaching thinking in students, the topic is intended to work and the way which the idea is wanted to get to them. Results are analysed and conclusions of work are exposed.